The Complexity of Abrasion Disaster Mitigation on Rupat Island - Dadang Mashur; Geovani Meiwanda; Khairul Amri; Mayarni Mayarni (Iapa Proceedings Conference, 2021)
Abrasion disasters and environmental issues are strategic issues that are widely studied from various study perspectives, this article is the result of research conducted by researchers from the perspective of public administration. The Abrasion Disaster on Rupat Island is a disaster that can cause various social and economic impacts on the community. In 2019, the abrasion rate on Rupat Island reached 6-8 meters. Rupat Island is also one of the outer islands of Indonesia which borders with neighbouring countries, namely Malaysia and is included in the National Tourism Strategic Area (KSPN). Therefore, the abrasion disaster that occurred on Rupat Island, Bengkalis Regency must be managed in order to minimize the impact of theabrasion disaster that occurred. Abrasion disaster management can be done one of them by means of abrasion disaster management or efforts made to regulate the reduction of abrasiondisaster risk. The purpose research is to know abrasion disaster management actors in Rupat Bengkalis and determine what course the limitations in disaster management abrasion in Rupat Bengkalis. This type of research is qualitative research using data collection methods through interviews and documentation. The findings in this study is that the management effort abrasion disaster in Rupat actor countermeasures abrasion in Rupat not maximized This is caused by things still are limitations in disaster management is done. The value in this study is that disaster management actors at the regional and central levels cooperate with each other in order to maximize disaster management efforts